Ischemic Postconditioning After Routine Thrombus Aspiration During Primary Percutaneous Coronary Intervention: Rationale and Design of the POstconditioning Rotterdam Trial. Issue 4 (10th September 2015) - Yetgin, Tuncay; van Kranenburg, Matthijs; ten Cate, Tim; Duncker, Dirk J.; de Boer, Menko‐Jan; Diletti, Roberto; van Geuns, Robert‐Jan M.; Zijlstra, Felix; Manintveld, Olivier C.
Abstract : Background: Whether ischemic postconditioning (IPOC) immediately after routine thrombus aspiration (TA) reduces infarct size (IS) in patients with ST‐segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) has not been established. Study design: The POstconditioning Rotterdam Trial (PORT) is a dual‐center, prospective, open‐label, randomized trial with blinded endpoint evaluation enrolling 72 subjects with first‐time STEMI, and an occluded infarct‐related artery (IRA) without collaterals undergoing PPCI. Subjects are randomized 1:1 to a strategy of IPOC immediately after TA followed by stenting of the IRA or to conventional percutaneous coronary intervention (PCI), including TA followed by stenting of the IRA (controls). Cardiac magnetic resonance imaging (MRI) is performed at 3–5 days after STEMI and at 3 months. The primary endpoint is IS at 3 months measured by delayed enhancement MRI. Other secondary endpoints include MRI‐derived microvascular obstruction (MVO), left ventricular ejection fraction, myocardial salvage index, enzymatic IS, ST‐segment resolution, myocardial blush grade, microcirculatory resistance, inflammation markers, and clinical events through 3‐month follow‐up. Conclusions: PORT is testing the hypothesis that adding IPOC (against lethal reperfusion injury) to TA (against distal embolization and MVO) is cardioprotective and reduces ultimate IS in STEMI patients undergoing PPCI ( Dutch Trial Register identifier: NTR4040). © 2015 Wiley Periodicals, Inc.